Comparison of root-associated communities of native and non-native ectomycorrhizal hosts in an urban landscape - Lothamer, K.; Brown, Shawn Paul; Mattox, J. D.; Jumpponen, Ari M. (My University, 2014)
Non-native tree species are often used as ornamentals in urban landscapes. However, their root-associated fungal communities remain yet to be examined in detail. Here, we compared richness, diversity and community composition of ectomycorrhizosphere fungi in general and ectomycorrhizal (EcM) fungi in particular between a non-native Pinus nigra and a native Quercus macrocarpa across a growing season in urban parks using 454-pyrosequencing. Our data show that, while the ectomycorrhizosphere community richness and diversity did not differ between the two hosts, the EcM communities associated with the native host were often more species rich and included more exclusive members than those of the non-native hosts. In contrast, the ectomycorrhizosphere communities of the two hosts were compositionally clearly distinct in nonmetric multidimensional ordination analyses, whereas the EcM communities were only marginally so. Taken together, our data suggest EcM communities with broad host compatibilities and with a limited numbers of taxa with preference to the non-native host. Furthermore, many common fungi in the non-native Pinus were not EcM taxa, suggesting that the non-native host communities may be enriched in non-mycorrhizal fungi at the cost of the EcM taxa. Finally, while our colonization estimates did not suggest a shortage in EcM inoculum for either host in urban parks, the differences in the fungi associated with the two hosts emphasize the importance of using native hosts in urban environments as a tool to conserve endemic fungal diversity and richness in man-made systems.
Keywords: Inoculum load; Ornamental trees; Pinus; Quercus; Urbanization